The Financial Coaching Advice Model: An Exploration into how it Satisfies Expectations of Quality Advice - Julie Knutsen; Robyn Cameron (Australasian Accounting, Business and Finance Journal, 2012)
For 20 years, the financial planning sector in Australia has been transitioning from a sales-orientated force to a profession of qualified and skilled practitioners. Today, the potential for professional financial planning advice to benefit Australians financially, economically and psychologically is recognised by government. Financially, these benefits include increased savings, less interest expense through faster debt reduction, higher investment returns and appropriate levels of insurance. Economically, a more financially literate society has the potential for less reliance on an already burdened social security system. Psychologically, the benefits include the peace of mind that comes from an individual being confident in financial matters. However, despite this level of recognition and development, national surveys have reported that only a small percentage of the population actually seek professional financial advice. The factors attributing to these low percentages included the gaps in financial literacy limiting an individual’s engagement in financial matters and consumer’s current mistrust of the financial advice business models that remain dominated by commission-driven product sales. These deficiencies have led some financial planning firms to break from financial product sales as the primary advice model and focus on financial coaching. Exploratory interviews with the practitioners and clients of a selected financial planning firm have generated insightful discussion into how a financial coaching advice model is achieving the financial, economic and psychological benefits recognised by government as the potential outcomes of professional financial advice. The aim of this paper is to present the findings from that discussion and demonstrate the opportunities embedded within a financial coaching advice model. It is argued that this discussion offers a foundation for future research direction in an area currently under researched in academic literature.
Keywords: Professional financial planning; financial advice; financial coaching; cognitive behavioural coaching; quality advice; grounded theory; client engagement; coaching